IMPLEMENTASI KURIKULUM 2013 DALAM PEMBELAJARAN IPS SISWA SMP ALKHAIRAT TANDAIGI KECEMATAN SINIU KABUPATEN PARIGI MUOTONG - Afdih, Afdih; Askar, Askar; Hamzah, Erni Irmayanti (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) UIN Datokarama Palu, 2022)
This article discusses the implementation of the 2013 curriculum in social studies learning for students at SMP Alkhairaat Tandaigi, Siniu District, Parigi Moutong Regency. The focus of the discussion in this study is how the social science teacher understands at Alkhairaat Tandaigi Middle School, Siniu District, Parigi Moutong Regency about the 2013 Curriculum and How to Implement the 2013 Curriculum in Social Sciences at Alkhairaat Tandaigi Middle School, Siniu District, Parigi Moutong Regency. The method that the author uses in this study is a qualitative research method. With data collection techniques including observation, interviews, and documentation. The results of this study indicate that the social studies teacher's understanding of the 2013 curriculum is that the 2013 curriculum is a follow-up to the previous curriculum. This competency-based 2013 curriculum focuses on the acquisition of certain competencies by students. Therefore, students are required to be more active and skilled at the time of learning. With the 2013 curriculum, it is not only focused on students, but teachers are also required to be more creative in teaching. Because the teacher is one of the human components in the teaching and learning process that plays a role in efforts to shape the behavior of students. And the implementation of the 2013 curriculum in social studies subjects was obtained from interviews with social studies teachers and school principals that had gone well. The implementation of the 2013 curriculum, which means that it has been applied in total using the 2013 curriculum. The obstacles in implementing the 2013 curriculum in social studies lessons at Al Khairaat Tandaigi Junior High School, Siniu District, Parigi Moutong Regency, namely, in implementing the 2013 curriculum, students and teachers need quite a long time to develop the curriculum. understand and adapt to the new model learning system offered by the government in the 2013 curriculum. With this method not all teachers are able to assess using 5M in the learning process, in the 2013 curriculum which is still difficult to apply Package books provided by the government are still lacking and limited facilities and infrastructure as learning media.